Pesto: Automated migration of DOM‐based Web tests towards the visual approach. (30th March 2018) - Leotta, Maurizio; Stocco, Andrea; Ricca, Filippo; Tonella, Paolo
Summary: Test automation tools are widely adopted for testing complex Web applications. Three generations of tools exist: first, based on screen coordinates; second, based on DOM–based commands; and third, based on visual image recognition. In our previous work, we proposed Pesto, a tool able to migrate second‐generation Selenium WebDriver test suites towards third‐generation Sikuli ones. In this work, we extend Pesto to manage Web elements having (1) complex visual interactions and (2) multiple visual appearances. Pesto relies on aspect‐oriented programming, computer vision, and code transformations. Our new improved tool has been evaluated on two Web test suites developed by an independent tester. Experimental results show that Pesto manages and transforms correctly test suites with Web elements having complex visual interactions and multistate elements. By using Pesto, the migration of existing DOM–based test suites to the visual approach requires a low manual effort, since our approach proved to be very accurate. Abstract : In this work, we proposed and experimented with a novel approach and its implementation, a tool called PESTO, able to transform DOM‐based Web test suites developed using Selenium WebDriver into visual test suites relying on the usage of Sikuli API. Experimental results show that PESTO manages and transforms correctly test suites with Web elements having complex visual interactions and multistate elements.